2016
DOI: 10.1002/ejp.939
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy fatty acids mediate analgesia in murine diabetic neuropathy

Abstract: Background Neuropathic pain is a debilitating condition with no adequate therapy. The health benefits of omega‐3 fatty acids are established, however, the role of docosahexaenoic acid (DHA) in limiting pain has only recently been described and the mechanisms of this action remain unknown. DHA is metabolized into epoxydocosapentanoic acids (EDPs) via cytochrome P450 (CYP450) enzymes which are substrates for the soluble epoxide hydrolase (sEH) enzyme. Here, we tested several hypotheses; first, that the antinocic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 61 publications
3
31
0
Order By: Relevance
“…Tumor sizing was measured using caliper, at the end of the experiment, the tumors were dissected, weighted and subjected to biochemical analysis. The EDPs are a synthetic mixture containing naturally occurring EDP regioisomers (7,8-, 10,11-, 13,14-, 16,17-, and 19,20-EDP), as we described [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Tumor sizing was measured using caliper, at the end of the experiment, the tumors were dissected, weighted and subjected to biochemical analysis. The EDPs are a synthetic mixture containing naturally occurring EDP regioisomers (7,8-, 10,11-, 13,14-, 16,17-, and 19,20-EDP), as we described [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Studies employing this technique demonstrated the dose dependent efficacy of the sEHI, and importantly, that as potent analgesics, the sEHI lacked rewarding effects in the absence of pain (Wagner, et al, 2014). Importantly, direct administration of EpFA also induced a conditioned response in diabetic mice (Wagner, et al, 2016). Further investigation in a naturally occurring Type I diabetic mouse model (Akita) demonstrated the efficacy of the sEHI (Wagner, et al, 2017).…”
Section: Seh As a Target For Painmentioning
confidence: 99%
“…This work demonstrated inhibiting sEH did not produce reward seeking behavior (a conditioned place preference) in naïve and sEH null mice. Additionally, direct administration the EpFA demonstrated both analgesic efficacy against neuropathic pain as well as a lack of rewarding side effects (Wagner, et al, 2016). …”
Section: Seh As a Target For Painmentioning
confidence: 99%
“…The EpFA are stabilized in vivo by the inhibition of the sEH and have demonstrated anti-inflammatory, antihypertensive, and analgesic properties [57]. The EpFA have also demonstrated efficacy against chemically induced diabetic neuropathy [8]. Here we use the Akita mouse model to inquire if sEH inhibition is analgesic in this naturally progressing disease, and importantly, if there are sexual dimorphisms in the pain responses.…”
Section: Introductionmentioning
confidence: 99%